Earthquake-Resistant Building : Buckling-Restrained Braced Truss-Girder Moment Frames (proposed) - Sugihardjo, Hidayat (IPTEK The Journal for Technology and Science, 2025)
This paper evaluates the inelastic behaviors of four Buckling-Restrained Braces (BRB) and two full scale Buckling-Restrained Braced Truss-girder Moment Frames (BRBTMF) by analytical and experimental means. The BRB section is strip plate core cased with rectangular hollow section, thus resulting in identical axial strengths of compression and tension. The BRBTMF proposed in this paper is the modification of The Special Truss Moment Frames (STMF) by replacing the X-bracing with the BRB. The conclusion of analytical studies is that frames proposed have better inelastic behavior than the other ductile frames. From the experimental analysis the BRBTMF have hysteretic curves in the 3% drift ratio to cyclic loading and result the cumulative ductility factor which has met the requirements of the hysteretic system structure.